Highly conductive single-molecule wires with controlled orientation by coordination of metalloporphyrins - Aragonès, A.; Darwish, Nadim; Saletra, W.; Pérez-García, L.; Sanz, F.; Puigmartí-Luis, J.; Amabilino, D.; Díez-Pérez, I. (American Chemical Society, 2014)
Porphyrin-based molecular wires are promising candidates for nanoelectronic and photovoltaic devices due to the porphyrin chemical stability and unique optoelectronic properties. An important aim toward exploiting single porphyrin molecules in nanoscale devices is to possess the ability to control the electrical pathways across them. Herein, we demonstrate a method to build single-molecule wires with metalloporphyrins via their central metal ion by chemically modifying both an STM tip and surface electrodes with pyridin-4-yl-methanethiol, a molecule that has strong affinity for coordination with the metal ion of the porphyrin. The new flat configuration resulted in single-molecule junctions of exceedingly high lifetime and of conductance 3 orders of magnitude larger than that obtained previously for similar porphyrin molecules but wired from either end of the porphyrin ring. This work presents a new concept of building highly efficient single-molecule electrical contacts by exploiting metal coordination chemistry.